Functionalizing self-assembled GaN quantum dot superlattices by Eu-implantation - Magalhães, S. (2010)
Self-assembled GaN quantum dots (QDs) stacked in superlattices (SL) with AlN spacer layers were implanted with Europium ions to fluences of 1013, 1014, and 1015 cm−2. The damage level introduced in the QDs by the implantation stays well below that of thick GaN epilayers. For the lowest fluence, the structural properties remain unchanged after implantation and annealing while for higher fluences the implantation damage causes an expansion of the SL in the [0001] direction which increases with implantation fluence and is only partly reversed after thermal annealing at 1000 °C. Nevertheless, in all cases, the SL quality remains very good after implantation and annealing with Eu ions incorporated preferentially into near-substitutional cation sites. Eu3+ optical activation is achieved after annealing in all samples. In the sample implanted with the lowest fluence, the Eu3+ emission arises mainly from Eu incorporated inside the QDs while for the higher fluences only the emission from Eu inside the AlN-buffer, capping, and spacer layers is observed. © 2010 American Institute of Physics